Inflammation Modifies the Paradoxical Association between Body Mass Index and Mortality in Hemodialysis Patients - Stenvinkel, Peter; Gillespie, Iain A.; Tunks, Jamie; Addison, Janet; Kronenberg, Florian; Drueke, Tilman B.; Marcelli, Daniele; Schernthaner, Guntram; Eckardt, Kai-Uwe; Floege, Juergen; Froissart, Marc; Anker, Stefan D. (Journal of the American Society of Nephrology, 2016)
High body mass index (BMI) is paradoxically associated with better outcome in hemodialysis (HD) patients. Persistent inflammation commonly features in clinical conditions where the obesity paradox is described. We examined the relationship between BMI and mortality in HD patients, accounting for inflammation, in a historic cohort study of 5904 incident HD patients enrolled in 2007-2009 (312 facilities; 15 European countries) with >=3 months of follow-up. Patients were classified by presence (n=3231) or absence (n=2673) of inflammation (C-reactive protein >=10 mg/l and/or albumin <=35 g/l). Patients were divided into quintiles by BMI (Q1-Q5: <21.5, 21.5-24.0, >24.0-26.4, >26.4-29.8, and >29.8 kg/m(2), respectively). Noninflamed patients in BMI Q5 formed the reference group. During a median follow-up period of 36.7 months, 1929 deaths occurred (822 cardiovascular), with 655 patients censored for renal transplantation and 1183 for loss to follow-up. Greater mortality was observed in inflamed patients (P<0.001). In fully adjusted time-dependent analyses, the all-cause mortality risk in noninflamed patients was higher only in the lowest BMI quintile (hazard ratio [HR, 1.80; 95% confidence interval [95% CI], 1.26 to 2.56). No protective effect was associated with higher BMI quintiles in noninflamed patients. Conversely, higher BMI associated with lower all-cause mortality risk in inflamed patients (HR [95% CI] for Q1: 5.63 [4.25 to 7.46]; Q2: 3.88 [2.91 to 5.17]; Q3: 2.89 [2.16 to 3.89]; Q4: 2.14 [1.59 to 2.90]; and Q5: 1.77 [1.30 to 2.40]). Thus, whereas a protective effect of high BMI was observed in inflamed patients, this effect was mitigated in noninflamed patients.
EVALuna2:3810